2021
DOI: 10.1108/el-04-2021-0082
|View full text |Cite
|
Sign up to set email alerts
|

Generation Z and intention to use the digital library: does personality matter?

Abstract: Purpose This study aims to evaluate the role of personality in digital library systems (DLS) adoption intention among Generation Z (Gen-Z) students. The study uses the unified theory of acceptance and use of technology-2 and the five-factor model to investigate personality’s influence on Gen-Z’s DLS adoption intention. Design/methodology/approach The study is a descriptive causal investigation based on primary data collected through a self-administered survey using pre-validated tools. The study uses structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In a future study, more parents of different types of schools and other Asian countries, as well as various types of electronic resources, such as e-news (Yu et al , 2021) and e-magazines (Wang et al , 2016), will be studied. It is also interesting to study the personality of parents and children in using digital resources (Sanjeev et al , 2022) and the obstacles to using digital libraries (Fernandes and Cendón, 2021) for children. Future studies should also analyse how parents’ reading habits and their use of digital resources impact their children’s reading skills with more respondents recruited.…”
Section: Discussionmentioning
confidence: 99%
“…In a future study, more parents of different types of schools and other Asian countries, as well as various types of electronic resources, such as e-news (Yu et al , 2021) and e-magazines (Wang et al , 2016), will be studied. It is also interesting to study the personality of parents and children in using digital resources (Sanjeev et al , 2022) and the obstacles to using digital libraries (Fernandes and Cendón, 2021) for children. Future studies should also analyse how parents’ reading habits and their use of digital resources impact their children’s reading skills with more respondents recruited.…”
Section: Discussionmentioning
confidence: 99%
“…People with high levels of openness are willing to try new things and to consider new and unconventional ideas [ 43 , 46 , 47 ]. People who are more open tend to trust computers and recent technologies more than those that score lower regarding this trait [ 48 , 49 ]. Research showed that openness to experience is significantly associated with willingness to accept the use of different forms of AR [ 50 , 51 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These digital libraries display the link between information, collections and technological progressions (Fritz et al , 2020). Over the years, the development of digital libraries has been a growing area of study such as in the context of users’ intention to acquire information and enhance their performance (Chang et al , 2009); users’ acceptance and utilization (Park et al , 2009); students’ use intention of electronic library resources (Joo and Choi, 2015); users’ satisfaction (Xu and Du, 2018; Soltani-Nejad et al , 2020); students’ satisfaction (Xu and Du, 2019); various types of big data resources and the value of services for users (Li et al , 2019); individual encounters with the datathon during COVID-19 (Fritz et al , 2020); the potential influence of personality traits on individuals’ intention to adopt among Gen-Z students (Sanjeev et al , 2021); users’ acceptance of blockchain technology for obtaining digital resources (Khan et al , 2022); research scholars’ usage and satisfaction (Iqbal et al , 2022) and students’ usage during COVID-19 (Habibi et al , 2022).…”
Section: Literature Review and Hypothesis Formulationmentioning
confidence: 99%